The effect of Saccharomyces cerevisiae CBS 493.94 level on in vitro fermentation using faecal inoculum from horses fed diets with different fibre concentrations - Santos, Ana S; Guedes, C.V.M; Ferreira, L. M. M; Evangelista, L; Gaspar, G; Bertin, G; Rodrigues, M.A.M (MTT, 2008)
According to regulations, 4 × 109 CFU / kg feed is the lowest dose of Yea-Sacc® recommended for horses. In order to decrease this dosage an experiment was conducted to test the effect of three levels of live yeast of Saccharomyces cerevisiae CBS 493.94 (Yea- Sacc®) on the in vitro digestibility and on the fermentation patterns using fecal inoculum from horses fed diets with different fiber concentrations. The three levels were 4.5 × 108, 9 × 108 and 4.5 × 109 CFU/ kg DM intake, and their influence were studied using the gas production method and in vitro batch incubations to estimate the digestibility of the diets and some end products of fermentation. Our data show that Yea-Sacc® incorporation level improved the in vitro fermentation of all studied diets. However, no significant improvement was observed with the increase of incorporation from 9 × 108 to 4.5 × 109 CFU / kg DM intake levels.
Keywords: Ko; Yea-Sacc®; gas production; in vitro digestibility; fermentation parameters; horse